Measurement and partitioning of in situ CO[subscript]2 fluxes in turfgrasses using a pressurized chamber - Bremer, Dale J.; Ham, Jay M. (My University, 2009)
Field measurements of photosynthesis in turfgrass often are conducted with handheld chambers that are temporarily placed over the canopy and soil. Because gas exchange measurements include soil respiration (R [subscript]s), results do not represent net canopy photosynthesis (P [subscript c,net]) but rather net ecosystem exchange of CO2 (NEE), or gross canopy photosynthesis (P [subscript g]) less the sum of canopy respiration (R [subscript]c]) and R [subscript]s. Chambers attached to steady-state, portable photosynthesis systems normally are partially pressurized which may partially suppress R [subscript]s (depending on pressure magnitude and soil moisture and type) and may overestimate NEE. Objectives of this research were to: 1) develop a chamber in which pressure could be manipulated; 2) measure CO2 fluxes at neutral pressure (chamber pressure equals atmospheric) to estimate NEE; 3) measure P [subscript]c,net by applying increasing pressure until R [subscript s] is prevented from entering the chamber; and 4) partition CO2 fluxes among P [subscript]g, R [subscript]c, and R [subscript] s. Pressure fluctuations of [plus or minus]1.0 Pa were uncontrollable which caused large differences in CO[subscript]2 exchanges near neutral pressure and prevented measurements of NEE. Chamber pressurization from 50 to 200 Pa suppressed most but not all R [subscript]s which disallowed measurement of P [subscript]cnet using a single pressurized reading. A new procedure provided estimates of P [subscript]c,net, R [subscript]c, and P [subscript]g from pressurized measurements of turf under sunlit and shaded conditions and from turf clipped at ground level. Flux from clipped plots under pressurization provided estimates of R [subscript]s that could not be suppressed with pressure. This was subtracted from pressurized readings over sunlit and shaded unclipped canopies to estimate P [subscript]c,net and R [subscript]c, respectively.
Keywords: Photosynthesis; Surface chamber; Turfgrass carbon balance; Chamber pressure effects